2018
DOI: 10.1093/cid/ciy665
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment Mortality Among Patients With Tuberculosis: A Prospective Cohort Study of 10 964 Patients in Vietnam

Abstract: Patients treated for tuberculosis had a markedly elevated risk of death, particularly in the post-treatment period. Interventions to reduce tuberculosis mortality must enhance the early detection of drug-resistance, improve treatment effectiveness, and address non-communicable diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 16 publications
4
32
0
1
Order By: Relevance
“…We observed that patients with tuberculosis died at a higher rate than the source population over 5 years of follow-up, similar to findings previously reported in India (SMR 6·1; for 2000–03) 10 . When considering those who survived the first year, we observed a SMR comparable to that reported in post-treatment cohorts in Israel (3·7; for 2000–10), 7 and Vietnam (4·0; for 2010–13) 11 . Although this study is restricted by not using individual data to build a cohort without tuberculosis and not disentangling excess mortality from tuberculosis itself or vulnerable conditions, we observed that patients with tuberculosis with vulnerable conditions had even higher excess mortality (SMR 8·1 over 5 years, and 5·3 for those who survived the first year), compared with the source population.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We observed that patients with tuberculosis died at a higher rate than the source population over 5 years of follow-up, similar to findings previously reported in India (SMR 6·1; for 2000–03) 10 . When considering those who survived the first year, we observed a SMR comparable to that reported in post-treatment cohorts in Israel (3·7; for 2000–10), 7 and Vietnam (4·0; for 2010–13) 11 . Although this study is restricted by not using individual data to build a cohort without tuberculosis and not disentangling excess mortality from tuberculosis itself or vulnerable conditions, we observed that patients with tuberculosis with vulnerable conditions had even higher excess mortality (SMR 8·1 over 5 years, and 5·3 for those who survived the first year), compared with the source population.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies showed that these conditions were associated with all-cause mortality, 3 particularly alcohol consumption, in high-income countries12, 28 and low-income and middle-income countries 10 . Although not estimated by a quantitative measure of association (eg, cause-specific HR), studies done in Israel 7 and Denmark 12 with death certificate data, together with the study from Vietnam, 11 which used verbal autopsy, reported a higher proportion of deaths probably associated with alcohol and drug use among patients with tuberculosis compared with the source population. We observed that, among patients with tuberculosis, lower acute respiratory infections and chronic respiratory diseases were the top causes of death, which is compatible with evidence showing post-tuberculosis lung sequelae 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. Einschränkung der Lungenfunktion) untersucht werden. Dies würde über das zeitliche Follow-up der meisten bisherigen internationalen Kohorten hinausgehen [17,18].…”
Section: Tuberkuloseunclassified